The impact of global drug policy on women : shifting the needle - Buxton, Julia; Margo, Giavana; Burger, Lona (Bingley, U.K. : Emerald Publishing Limited, 2020)
The ebook edition of this title is Open Access and freely available to read online. The international strategy of criminalising the cultivation, manufacture, distribution and use of certain psychoactive substances has failed to achieve a 'drug free world'. Examining the impact of drug criminalisation and enforcement on a previously overlooked demographic, this edited collection argues that women are negatively and disproportionately affected by this flawed policy approach. Addressing the lack of attention on the experience of women, this collection details the challenges women face in accessing appropriate treatment and services, the stigmatisation and marginalisation resulting from engagement in illegal drug markets, the violence that women are exposed to, and the punitive sentences imposed on women for drug related offences. Bringing together an international group of academics, advocates, activists and those with lived experience, the editors offer a rounded and realistic view from women's perspectives. In doing so, they facilitate a call for feminist and women's organisations to embrace drug policy reform, and for international and national level drug control authorities to better engage women as stakeholders.
Prelims -- Introduction -- Chapter 1: International drug policy in context -- Chapter 2: Gendering drug policy -- Chapter 3: Women and the politics of pleasure in critical drug studies -- Chapter 4: Fiona's story -- Chapter 5: Nexus of risk: the co-occurring problems of gender-based violence, HIV and drug use among women and adolescent girls -- Chapter 6: Risk behaviours among older women who use drugs -- Chapter 7: Women who use drugs and mental health -- Chapter 8: Access barriers to health services for women who use drugs in Eastern Europe and Central Asia -- Chapter 9: Suzanne's story -- Chapter 10: Sex work, justice and decriminalisation: beyond a politics of recognition in promoting a social justice response to women at the margins -- Chapter 11: Women incarcerated for drug-related offences: a Latin American perspective -- Chapter 12: Policing and sentencing practices in Russia and their impacts on women who use drugs -- Chapter 13: Women, drug policy and the Kenyan prison system -- Chapter 14: Drug policy and women prisoners in Southeast Asia -- Chapter 15: The increase in women who use drugs in Zimbabwe -- Chapter 16: Women as actors in the drug economy -- Chapter 17: Women's involvement in organised crime and drug trafficking: a comparative analysis of the Sinaloa and Yamaguchi-gumi organisations -- Chapter 18: From the Colombian Coca Fields: peasant women amid the war on drugs -- Chapter 19: 'Las Empoderadas' women coca growers building territorial peace -- Chapter 20: Unseen and unheard: the women in Duterte's war on drugs -- Chapter 21: Happy's story -- Chapter 22: Overdose risks and prevention strategies for pregnant women in New York City -- Chapter 23: Patterns of recreational drug use and harm reduction strategies among women at music festivals: the case of Hungary and Poland -- Chapter 24: Queer feminine identities and the war on drugs -- Chapter 25: Best practices in reaching 'hidden' populations and harm reduction service provision -- Chapter 26: A mother's story -- Chapter 27: Drug users as stakeholders in drug policy: questions of legitimacy and the silencing of the happy drug user -- Chapter 28: Improving drug policy metrics and advancements in measuring gender-based drug policy outcomes -- Chapter 29: Towards an abolitionist drug policy reform -- Chapter 30: Women who use drugs: resistance and rebellion -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Women -- Drug use; Drug control; Social Science -- Women's Studies; Drugs trade, drug trafficking